МУСИҚАЛИ ТЕАТРДАГИ МАҚОМДОН АЁЛЛАР (ХХ асрнинг биринчи ярми) - Пирматова, Н. (SCIENCE and SOCIETY, 2022)
The combination of theater and makoms and today has received an unusual modern shade. This gave a great impetus to the wider promotion of the Uzbek national musical art, our makom. In fact, in the first half of the twentieth century, creative people who worked in musical theater were professionally engaged in both acting and makom performance, and brilliantly played any role. This article will tell about female singers who worked in musical theater in the first half of the XX century. At the same time, a topical issue will be touched upon on this topic.
Keywords: musical theater; makom; classical works; acting; singing; makom theater